Association of T2 relaxation time determined by magnetic resonance imaging and intramyocellular lipid content of the soleus muscle in healthy subjects - Sakurai, Yuko (Blackwell Publishing Ltd, 2011)
The level of intramyocellular lipids (IMCL) is a physiological marker of skeletal muscle function. (1)H‐magnetic resonance spectroscopy (MRS) is an established method to measure IMCL contents in vivo. However, all of the MR systems do not always contain measurement instruments for (1)H‐MRS, thus in a clinical setting, alternative methods for estimation of IMCL content are needed. Here, we investigated the association between T1 and T2 relaxation times, determined by MR imaging, and IMCL measured by (1)H‐MRS in the soleus and tibialis anterior muscles of 15 healthy male subjects. Intriguingly, in the soleus muscle, but not in the tibialis anterior muscle, T2 relaxation time correlated significantly with IMCL (r = 0.65, P < 0.05). The result suggests the possibility that T2 relaxation time of the soleus muscle can be used to estimate IMCL in a clinical setting. (J Diabetes Invest, doi: 10.1111/j.2040‐1124.2011.00108.x, 2011)